2016
DOI: 10.4143/crt.2015.425
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quality of Life and Sexuality between Cervical Cancer Survivors and Healthy Women

Abstract: PurposeThe purpose of this study is to compare quality of life (QoL) and sexual functioning between sexually active cervical cancer survivors and healthy women.Materials and MethodsIn this cross-sectional study, propensity-score-matched cervical cancer survivors (n=104) and healthy women (n=104) were compared. All women had engaged in sexual activity within the previous 3 months, and cervical cancer survivors showed no evidence of disease after primary treatment. QoL and sexual functioning were assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
4
32
1
6
Order By: Relevance
“…However, a study done in the United Kingdom showed that diarrhea was the most frequently reported symptom [24]. This might be due to the different Bae and Park (2016), that poor body image is due to low self-esteem observed among women who have not yet children [25]. Additionally, shame and regret contributed significantly to poorer body image and lower sexual/vaginal functioning in younger age groups [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study done in the United Kingdom showed that diarrhea was the most frequently reported symptom [24]. This might be due to the different Bae and Park (2016), that poor body image is due to low self-esteem observed among women who have not yet children [25]. Additionally, shame and regret contributed significantly to poorer body image and lower sexual/vaginal functioning in younger age groups [26].…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line other study in about quality of life in Indonesia and other country studies where all means of global health status were >50 in their studies. 7,8 The high mean of quality of life is explained in several studies. They state that the low quality of life is significantly related to low social support.…”
Section: Quality Of Life Of Cervical Cancer Patient With Supportive Fmentioning
confidence: 99%
“…16 This pattern is like what was observed in a study in Korea. 17 Furthermore, study in Iran states that global health scale has significant relation with social function, nauseous and vomiting, dyspnea, insomnia, loss of appetite, financial problem, peripheral neuropathy, and menopausal symptoms. 18 All of these three studies has similar pattern where sexual activity and sexual pleasure decrease significantly.…”
Section: Quality Of Life Of Cervical Cancer Patient With Supportive Fmentioning
confidence: 99%
“…It is estimated that cervical cancer accounted for 3,100 (2.2%) of all new cancers and 761 (2.6%) of all cancer deaths among Korean women in 2015 (12). Human papillomavirus (HPV) infection is the main cause of cervical cancer, and infection typically occurs through sexual behavior (34).…”
Section: Introductionmentioning
confidence: 99%